Indoor-outdoor relationship of carcinogenic polycyclic aromatic hydrocarbons in Portuguese preschools - K. Slezakova (2015)
Children represent one of the most vulnerable groups in society. The detailed characterizationof pollution (both indoors and outdoors) of schools is of great importance, since it may allowpreventing potential risks to children health. Yet the information related to carcinogeniccompounds, such as some polycyclic aromatic hydrocarbons (PAHs) in child educationalsettings is very limited. Thus the aim of this work was to assess indoor and outdoor levels ofPAHs at Portuguese preschools (3-5 years old children) in urban areas with emphasis oncarcinogenic compounds, and to identify the main sources of indoor PAHs.Eighteen PAHs (16 considered by USEPA as priority pollutants, and dibenzo[a,l]pyrene andbenzo[j]fluoranthene, the latter recommend EU Directive 2008/50/EC) were collected during 45days of spring 2013 at two preschools (PS1, PS2) situated in two different (and distant fromeach other) urban areas in north of Portugal. Nine carcinogenic PAHs were included:benzo[a]pyrene (known carcinogen) and other 8 probable (benz[a]anthracene,dibenz[a,h]anthracene, dibenzo[a,l]pyrene) or possible (naphthalene, chrysene,benzo[b]fluoranthene, benzo[k]fluoranthene and indeno[1,2,3-c,d]pyrene) carcinogens. PAHs inPM2.5 (particulate matter with aerodynamic diameter < 2.5 m) were simultaneously collectedboth indoors (classroom, playrooms) and outdoors (playground and preschool yards).Quantification of PAHs was performed by microwave-assisted extraction combined with liquidchromatography with fluorescence and photodiode array detection. Total levels of 18 PAHs(ΣPAHs) were 2.6 and 3.2 higher in indoor and outdoor air of PS1 than at PS2. Compositionalprofiles were though similar at both preschools with 5-6 ring PAHs being the most abundant.Dibenz[a,h]anthracene and benzo[b]fluoranthene (both class 2A carcinogens) were thepredominant individual PAHs at both preschools. Nine carcinogenic compounds (ΣPAHscarc)accounted for 73 and 74% of indoor particulate PAH content at PS1 and PS2, respectively;outdoors the corresponding ΣPAHscarc composed 66% and 71% of ΣPAHs. Analysis of I/O ratiosof ΣPAHscarc suggested that outdoor emissions were a significant contributor to indoorcarcinogenic PAHs at both schools. ΣPAHscarc exceeded the recommended EU guideline valueof 1 ng m-3(100% of days at PS1, both indoors and outdoors; >65% samples at PS2) for thetotal content in PM10 averaged over a calendar year. Therefore, in order to prevent risks tochildren health it necessary to establish and implement target values of carcinogeniccomponents in indoor particles of smaller sizes (i.e. PM2.5).